Conundrum in an asthma exacerbation. (10th May 2016) - Isaac, Barney Thomas Jesudason; McLellan, Thomas; Samuel, Johnson; Yung, Bernard
Abstract : A 66-year-old man, an asthmatic, presented with symptoms suggestive of an acute exacerbation of asthma. His arterial blood gas revealed type 1 respiratory failure (PaO2 <8 kPa or 60 mm Hg with normal or low PaCO2 ) with a compensated lactic acidosis. He was treated for an asthma exacerbation and sepsis. Despite treatment, his respiratory rate remained elevated although his hypoxaemia improved. There was progressive worsening of the lactic acidosis. Treatment for sepsis was augmented. Peak flow measurements were not used to assess the severity of his exacerbation nor his response to treatment. An alternate diagnosis of acute coronary syndrome with acute pulmonary oedema was made and his asthma treatment was stopped. This coincided with a decline in his serum lactate. A diagnosis of salbutamol-induced lactic acidosis (SILA) was made. SILA is a relatively common complication of salbutamol therapy in moderate/severe asthma exacerbations. It is caused by a mechanism different from the lactataemia that is associated with septic shock and life-threatening asthma.